2006
DOI: 10.1111/j.1440-1819.2006.01512.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of venlafaxine extended release versus paroxetine for treatment of patients with generalized anxiety disorder

Abstract: This trial was to evaluate the efficacy and tolerability of venlafaxine extended release (XR) and paroxetine for treatment of patients with generalized anxiety disorder (GAD). Sixty patients who met DSM-IV criteria for GAD were randomly assigned to either venlafaxine XR or paroxetine for 8 weeks. Efficacy was assessed with the Hamilton Rating Scale for Anxiety (HAM-A) and Clinical Global Impression-Severity of Illness (CGI-S) scale at the baseline, week 1, week 4, and week 8. The side-effects were collected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 11 publications
1
14
0
1
Order By: Relevance
“…In contrast to duloxetine, Tang et al reported that fluoxetine showed equivalent efficacy either on HAM-A scores’ reduction or response rate at the end of a 6-week trial 45. These results were consistent with several RCTs in Western countries that directly compared different SSRIs and SNRIs, in which no statistically significant difference was found between them 46,47. Although there is less available data, it implies that fluoxetine can also be utilized as an effective SSRI in treating GAD.…”
Section: Comparative Safety Tolerability and Efficacy Of Fluoxetinesupporting
confidence: 89%
“…In contrast to duloxetine, Tang et al reported that fluoxetine showed equivalent efficacy either on HAM-A scores’ reduction or response rate at the end of a 6-week trial 45. These results were consistent with several RCTs in Western countries that directly compared different SSRIs and SNRIs, in which no statistically significant difference was found between them 46,47. Although there is less available data, it implies that fluoxetine can also be utilized as an effective SSRI in treating GAD.…”
Section: Comparative Safety Tolerability and Efficacy Of Fluoxetinesupporting
confidence: 89%
“…Similar evidence exists for paroxetine [546,547,553-558] supporting its use as a first-line option. Paroxetine CR has a similar active ingredient, and although there are less data supporting its use, it is likely interchangeable with paroxetine as a first-line agent (Level 3) [564,565].…”
Section: Generalized Anxiety Disordermentioning
confidence: 62%
“…Paroxetine CR has a similar active ingredient, and although there are less data supporting its use, it is likely interchangeable with paroxetine as a first-line agent (Level 3) [564,565]. In head-to-head comparisons, the efficacy of SSRIs and SNRIs appear to be similar [546,547,549,556,558,570,571]. Some data suggest that escitalopram may be less effective than venlafaxine XR [548] or quetiapine XR [551].…”
Section: Generalized Anxiety Disordermentioning
confidence: 99%
“…Both SSRIs and NE or NE/dopaminespecific drugs have been used in the treatment of GAD (Goodman, 2004), thus, it is possible to speculate that dual 5-HT/NE reuptake inhibitors may have greater efficacy than single reuptake inhibitors. Although recent studies comparing venlafaxine (75 mg and 150 mg/day) to paroxetine (40 mg/day) in GAD (Kim et al, 2006) and in panic disorder (Pollack et al, 2007) showed no significant differences between the two treatment groups, another study showed some differences in the treatment of panic disorder with venlafaxine 225 mg/day versus paroxetine 40 mg/day. As the NE reuptake effects of venlafaxine are evident at higher doses , these data provide some evidence of a differential effect of dual reuptake inhibitors versus SSRIs on anxiety disorders.…”
Section: Efficacy Of Dual Reuptake Inhibitors Efficacy In Depressionmentioning
confidence: 96%